Perancangan Sistem Informasi Rekam Medis Pasien Elektronik Terpusat (Studi Kasus : Kota Madya DENPASAR) - Adiputra, I Made Swasta; Sutanto, Teguh; Nurcahyawati, Vivine (Jurnal JSIKA, 2012)
Along with the development of information and communication technology (ICT), which has been a big influence for change in all sectors, including health, especially in the medical record is called the electronic medical record. Basically the electronic medical record is the use of electronic methods for collecting, storing, processing, and accessing patient records in hospitals that have been stored in a multimedia database management system, bringing together various sources of medical data. Often problems arise no link between their respective health care providers in terms of information on the medical record. Though patients may have a medical examination at health care providers vary at any given time. It leads to the same checks occur repeatedly. Whereas previous medical records are very useful in further medical examination. From some of the problems mentioned above have designed a centralized electronic medical record system that accommodates one patient´s medical record in a centralized database for the purpose of patient records are stored in a single database storage. So if one day patients already enrolled in the system, if referred from one hospital to another hospital in the region, the data can be viewed and accessed on the basis of data from hospitals or health care providers who have joined in this system. With this system helps to reduce the possibility of misdiagnosis. Keywords: Information Systems, Patient Electronic Medical Records, Electronic Medical Record Patient Centered.